2018
DOI: 10.1021/acs.nanolett.8b00894
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Imaging the Oxygen Reduction Reactions of Solid State Na–O2 Batteries with CuO Nanowires as the Air Cathode

Abstract: We report real time imaging of the oxygen reduction reactions (ORRs) in all solid state sodium oxygen batteries (SOBs) with CuO nanowires (NWs) as the air cathode in an aberration-corrected environmental transmission electron microscope under an oxygen environment. The ORR occurred in a distinct two-step reaction, namely, a first conversion reaction followed by a second multiple ORR. In the former, CuO was first converted to CuO and then to Cu; in the latter, NaO formed first, followed by its disproportionatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…Similar to Luo et al's work on Li–O 2 batteries, Kwak et al uncovered the reaction mechanism of single carbon nanotube Na–O 2 batteries using ETEM . Liu et al also reported the ORR of a CuO nanowire cathode in solid‐state Na–O 2 batteries probed by in situ TEM within an environmental chamber …”
Section: Energy Storagementioning
confidence: 71%
See 1 more Smart Citation
“…Similar to Luo et al's work on Li–O 2 batteries, Kwak et al uncovered the reaction mechanism of single carbon nanotube Na–O 2 batteries using ETEM . Liu et al also reported the ORR of a CuO nanowire cathode in solid‐state Na–O 2 batteries probed by in situ TEM within an environmental chamber …”
Section: Energy Storagementioning
confidence: 71%
“…In situ TEM has been widely applied to reveal the underlying mechanisms of rechargeable batteries, including LIBs, Li–O 2 batteries, Li–S batteries, lithium metal batteries, sodium‐ion batteries, sodium–O 2 batteries, and Li–Se batteries …”
Section: Energy Storagementioning
confidence: 99%
“…c) Reproduced with permission. [ 260 ] Copyright 2019, American Chemical Society. d) O 2 /O 2 − crossover prevention through SSEs for dendrite‐free solid‐state Na–O 2 batteries.…”
Section: Interfaces In Next‐generation All‐solid‐state Batteriesmentioning
confidence: 99%
“…Different form the final reaction products of NaO 2 in the liquid electrolyte based Na‐O 2 batteries, in situ TEM of all‐solid‐state Na–O 2 cells showed that the NaO 2 was formed first and then disproportionated to Na 2 O 2 and O 2 in the discharging (Figure 15c). [ 260 ] In addition, carbonate was absent during battery cycling. Similar to the all‐solid‐state sodium metal batteries, the anode interfaces of all‐solid‐state Na–O 2 batteries also suffer from the dendrite issues.…”
Section: Interfaces In Next‐generation All‐solid‐state Batteriesmentioning
confidence: 99%
“…After fully charged, the residual parasitic shells remained. More recently, Peng and co‐workers reported an in situ TEM study on a Na–O 2 system using CuO nanowires as the air cathode . They observed an irregular shape thin film‐like NaO 2 /Na 2 O 2 /Na 2 O mixture as the discharge product.…”
Section: Introductionmentioning
confidence: 99%